Mitogenome phylogeny reveals Indochina Peninsula origin and spatiotemporal diversification of freshwater crabs (Potamidae: Potamiscinae) in China. (28th June 2021) - Pan, Da; Shi, Boyang; Du, Shiyu; Gu, Tianyu; Wang, Ruxiao; Xing, Yuhui; Zhang, Zhan; Chen, Jiajia; Cumberlidge, Neil; Sun, Hongying
Abstract: The Asian potamid subfamily Potamiscinae is the most species‐rich group of primary freshwater crabs in the world, and a large number of these (318 species in 52 genera) are found in China where they exhibit a remarkably high rate of endemism. However, the evolutionary history and phylogenetic relationships of this subfamily is still poorly understood and the hypothesis that the Chinese potamids originated in the Indochina Peninsula has yet to be tested using a modern phylogeographic reconstruction and molecular dating methods. Here we analyze the phylogenetic relationships and biogeographic history of the Chinese potamiscines based on whole mitogenomes of 72 species of Asian freshwater crabs representing 65% of the potamiscine genera found in China, including new mitogenome sequences for 57 species. The mitogenomic phylogeny generated four separate clades: Southwest China (SWC), Indochina‐Southwest China (ISWC), Central China (CC), and South China‐adjacent Islands (SCI). Our results suggest that the Chinese potamiscine fauna most likely originated in Indochina during the Eocene. The establishment of the East Asian monsoon during the Eocene/Oligocene resulted in major climate changes that coincide with the local diversification of the CC and SCI clades. In addition, diversification of two other clades (ISWC and SWC) may have been driven by past large scale environmental changes taking place at that time such as increased local precipitation and expanding freshwater habitats associated with the uplifting of the Hengduan Mountains. In addition, our phylogenies did not support monophyly for six currently recognized potamiscine genera, highlighting the need for further taxonomic revisions of this fauna. The broad taxonomic sampling and well‐supported molecular phylogenies used here allow for the updating of our understanding of the evolutionary origins and diversification of the potamiscine freshwater crabs in China.